Sustainable Development and Resource Productivity The Nexus Approaches - Lehmann, Harry (Factor X: Studies in Sustainable Natural Resource Management, 2021)
The fourth Factor X publication from the German Environment Agency (Umweltbundesamt, UBA), Sustainable Development and Resource Productivity: The Nexus Approaches explores the interdependencies of sustainable development paths and associated resource requirements, describing and analysing the necessities for a more resource efficient world. The use of and competition for increasingly scarce resources are growing worldwide with current production and consumption patterns of industrialised economies soon to reach the point where the ecosphere will be overtaxed far beyond its limits. Against this background, this volume examines the important initiatives to monitor resource use at the international, EU and national level. The current trends and challenges related to sustainable resource use are discussed, including international challenges for a resource efficient world, megatrends, justice and equitable access to resources. In the second part of the book, contributions examine implementation strategies. They assess the concept known as circular economy and discuss the theory of growth and the role of the financial and education systems. The final section places special emphasis on practical examples. Overall, the book presents concrete ways and examples of achieving more sustainability in practice. Discussing solutions for a more sustainable use of natural resources, this book is essential reading for scholars and students of natural resources and sustainable development and decision-makers and experts from the fields of policy development, industry and civil society.